Factors Affecting Medication Adherence and the Success of Pulmonary Tuberculosis Therapy in Several Community Health Centers in Ambon City - Surtia, Surtia; Prima, Sylvia Rizky (Riviera Publishing, 2025)
This study examines the Factors Affecting Medication Adherence and the Success of Pulmonary Tuberculosis Therapy in Several Community Health Centers in Ambon City. Tuberculosis (TB) remains an infectious disease and a global health challenge, including in Indonesia. The success of TB therapy is highly dependent on the patient's adherence to the prescribed treatment. This study aims to analyze the factors that affect the adherence of pulmonary TB patients and their relationship with therapy success. The study design is observational with a cross-sectional approach, conducted both retrospectively and prospectively on pulmonary TB patients at several health centers in Ambon City. Data were collected through questionnaires and patient medical records. A sample of 150 respondents was selected using the purposive sampling method. The analysis was performed using the chi-square test and logistic regression. The results showed that family support, health worker support, and access to health facilities had a significant effect on patient compliance. Meanwhile, education and knowledge did not have a significant influence. The analysis also indicated a significant relationship between medication adherence and therapy success. Family support emerged as the most dominant factor influencing adherence. These findings highlight the importance of a holistic approach in TB management, particularly by strengthening social support and primary health services. Recommendations include increasing the educational role of pharmacists and implementing regular compliance monitoring. Further research is suggested to conduct longitudinal studies and explore psychosocial and cultural factors.